2021
DOI: 10.3389/fmolb.2021.639184
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced siRNA Delivery and Selective Apoptosis Induction in H1299 Cancer Cells by Layer-by-Layer-Assembled Se Nanocomplexes: Toward More Efficient Cancer Therapy

Abstract: Nanotechnology has made an important contribution to oncology in recent years, especially for drug delivery. While many different nano-delivery systems have been suggested for cancer therapy, selenium nanoparticles (SeNPs) are particularly promising anticancer drug carriers as their core material offers interesting synergistic effects to cancer cells. Se compounds can exert cytotoxic effects by acting as pro-oxidants that alter cellular redox homeostasis, eventually leading to apoptosis induction in many kinds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 72 publications
(83 reference statements)
2
8
0
Order By: Relevance
“…This observation may have ensued due to the use of dried samples to carry the TEM analysis, whereas in the DLS the hydrodynamic size of NPs is was measured instead. This is while the TEM image of CSNPs (Figure 2(j)) like our previous report is presented with an undefined shape having heterogeneous morphology 50 …”
Section: Resultssupporting
confidence: 73%
“…This observation may have ensued due to the use of dried samples to carry the TEM analysis, whereas in the DLS the hydrodynamic size of NPs is was measured instead. This is while the TEM image of CSNPs (Figure 2(j)) like our previous report is presented with an undefined shape having heterogeneous morphology 50 …”
Section: Resultssupporting
confidence: 73%
“…One of the reasons for the toxicity of Se for cancer cells as compared to normal somatic cells is the more reducing environment of cancer cells, which stimulates the formation of Se–S adducts from Se compounds [ 142 ]. Such Se–S adducts can mimic cystine and mixed disulfides, causing enhanced receptor-mediated uptake of Se by cancer cells [ 142 , 143 , 144 , 145 , 146 ].…”
Section: The Role Of Senp In Medicine and Human Healthmentioning
confidence: 99%
“…It was found that LBL-Se-NC is able to selectively induce apoptosis in 32% of human non-small cell lung carcinoma (H1299 cells), which is 5.7 times more than in normal NIH3T3 cells (mouse embryonic fibroblasts). When cancer cells were treated with the CS-NC complex in the same concentration range, there was no clear difference in the viability of these cells compared to normal cells, which indicated the selective and effective induction of apoptosis by LBL-Se-NC nanoparticles [ 146 , 166 ].…”
Section: The Role Of Senp In Medicine and Human Healthmentioning
confidence: 99%
“…A distinct field of research and development of these systems is the use of solid (metal) nanoparticles enclosed in a shell and serving as a carrier of a nucleic acid. For instance, there are reports on the efficient delivery of small interfering RNA (siRNA) via gold nanoparticles (AuNPs) [9] and selenium nanoparticles [10] coated with chitosan and gold nanorods covered with two layers of polyelectrolytes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our study was aimed at creating multilayer nanoconstructs (MLNCs) based on spherical AuNPs on whose surface an siRNA layer is adsorbed and surrounded by a lipid (siRNA) via gold nanoparticles (AuNPs) [9] and selenium nanoparticles [10] coated with chitosan and gold nanorods covered with two layers of polyelectrolytes [11].…”
Section: Introductionmentioning
confidence: 99%